Optimización de la calidad de un suelo agrícola por la aplicación de compost y abono sintético. Pampa del Arco, Ayacucho - Tineo Bermúdez, Alex (2015)
To determine the mix of fertilizers, natural and synthetic, that optimize the quality of an agricultural soil, the present work was carried out in Pampa del Arco, Ayacucho, with agricultural soil at rest (for five years) under cover of Pennisetum clandestinum. The experimental unit consisted of plastic buckets for 20 kg of soil with tomato cultivation. The July 3 design was used for two factors (a: natural fertilizer, compost; b: synthetic fertilizers, NPK). Soil quality and crop health were evaluated. The results found allow us to conclude the following: 1. The quality of the soil undergoes significant changes according to the mix of fertilizers, being more damaging those that carry high levels of synthetic fertilizer; On the contrary, compost contributes to maintaining an adequate rate of water infiltration in the soil profile. The application of synthetic compost, without compost, affects the microbial activity of the soil; 2. The least negative impact on water infiltration in the soil profile is achieved by applying mixtures of a minimum of 5 t.ha-1 of compost with 80-90-70 kg.ha-1 of NPK, or 7.5 t. ha-1 of compost with 160-180-140 kg.ha-1 of NPK; 3. The models that predict the influence of organic manure (compost) and synthetic manure on soil quality and crop health are: Y = 22.74 + 2.0949X1 - 4.3154X2 + 0.8430X1² - 0.5648X2² + 0.2771X1X2, for water infiltration; Y = 805.9 + 35.98462X1 + 52.72179X2 + 2.20291X1² - 10.23337X2² - 9.05208X1X2, for tomato yield.